Transforming healthcare delivery: a descriptive study of a novel provider-to-provider virtual care platform - Tennankore, Karthik; Jones, Jennifer; Miller, Ashley; Adib, Ashfaq; Mathew, Shan; Rasic, Daniel; Cookey, Jacob (Frontiers in Public Health, 2023)
Introduction: Addressing challenges in access to specialty care, particularly long wait times and geographic disparities, is a pressing issue in the Canadian healthcare system. This study aimed to evaluate the impact and feasibility of provider-to-provider phone consultations between primary care providers (PCPs) and specialists using a novel virtual care platform in Nova Scotia (Virtual Hallway).We conducted a cross-sectional survey over five months, involving 211 PCPs and 34 specialists across Nova Scotia. The survey assessed the need for formal inperson referrals as well as clinician satisfaction. Statistical methods included descriptive statistics and the one-sample t-test.We found that 84% of provider-to-provider phone consultations negated the need for an in-person specialist referral. It was also reported that 90% of patients that did require in-person consultation had enhanced care while they awaited an in-person appointment with a specialist. Very high levels of satisfaction were reported among both PCPs and specialists, and there was a noticeable increase in billing volumes related to these consultations as measured by provincial billing codes.The findings indicate that provider-to-provider phone consultations are feasible, well-accepted and also effective in reducing the need for in-person specialist visits. This approach offers a promising avenue for alleviating waitlist burdens, enhancing the quality of care, and improving the overall efficiency of healthcare delivery.